Lựa chọn công nghệ khai thác hợp lý cho khoáng sàng Kali Noongbok-CHDCND Lào - Lê, Huy Hoàng (2011)
Tác giả: Lê Huy Hoàng, TS; Nguyễn Huy Cương, KS; Hoàng Thị Hải Vân, KS; Nguyễn Chí Công, KS -- Từ khóa: Muối mỏ; Khai thác muối mỏ